Open regionalism : Latin America and the Caribbean in the global economy (UN ECLAC Port of SpainTT, 1996)
Presents descriptive statistics on the composition of trade in the region, by principal direction of trade flows. Analyses some of the most indicative trends in world trade. Poses a series of questions concerning trade and growth in the context of the current process of increasing integration between national markets.
DC